Bawal ang bastos developing a community-based campaign plan to convey the protective measures of Republic Act No. 11313, otherwise known as the Safe Spaces Act of 2019, to the Residents of Barangay Magugpo East, Tagum City - Zafra, Hannah Grace C. (2023)
Despite the implementation of Republic Act No. 11313, known as the Safe Spaces Act of 2019, manifestations of gender-based sexual harassment still persist in Barangay Magugpo East, Tagum City, Davao del Norte. This study focused on conveying the protective measures of the law to the residents of the aforementioned community by developing a community-based communication campaign plan. The study used Social Cognitive Theory to analyze the respondents? experiences of gender-based sexual harassment and awareness of the aforementioned law, while the Social Marketing Theory was used to develop the community-based campaign plan. Using the mixed-methods approach, data was gathered among 12 selected residents of the community through in-depth interviews and survey questionnaires. Three community leaders who were designated as Anti-Sexual Harassment Enforcers also stood as key informants. The formative research explored the respondents? lived experiences and prior knowledge of the protective measures of the law, as well as their sociodemographic profile, media preferences, and information source. The study revealed the prevalence of the different manifestations of gender-based sexual harassment and its detrimental and perilous consequences on the victims. The study?s respondents also had limited knowledge of the law and perceived its ineffective implementation due to the persistence of such misconduct in the community and lack of information dissemination. Thus, the developed community-based campaign plan was inculcated with the appropriate messages, strategies, and approaches to heighten public awareness and disseminate information on the issue, thereby contributing to efforts to raise awareness and change attitudes, perceptions, and behavior toward them.